PENGARUH MODEL PEMBELAJARAN VISUAL, AUDITORY, KINESTHETIK (VAK) TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS V UPTD SD NEGERI 39 PAREPARE - Usman; Nur Ilmi; Nurul Ain Mansyur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the description of the ability to write student poetry and the effect of the Visual, Auditory, Kinesthetic (VAK) learning model on the ability to write poetry of class V UPTD SD Negeri 39 Parepare students. The approach used is a quantitative approach with a type of pre-experimental research in the form of Pretest-Posttest One Group Only design. The population in this study were all UPTD SD Negeri 39 Parepare students, while the samples were fifth grade students. The research data was obtained by giving a poetry writing test. The data analysis technique is the Paired sample t-test. Based on the results of inferential statistical analysis showed Sig. (2-tailed) = 0.000 <0.05, so H_0 is rejected and H_1 is accepted. Thus, the conclusion of this study is that there is an increase in the value of students' poetry writing ability before and after being given teaching in the form of Visual, Auditory, Kinesthetic (VAK) learning models in class V UPTD SD Negeri 39 Parepare.